Thermal and non-thermal processing effect on açai juice composition. (October 2020) - Linhares, Maria de Fátima D.; Alves Filho, Elenilson G.; Silva, Lorena Mara A.; Fonteles, Thatyane V.; Wurlitzer, Nédio Jair; de Brito, Edy S.; Fernandes, Fabiano A.N.; Rodrigues, Sueli
Graphical abstract: Highlights: Non-thermal processing increased the amounts of glucose and fructose, and betaine. Thermal processing increased the concentration of fatty acids and phenolic compounds. HSTS and UHT better preserved the bioactive compounds along with the storage. Microbial inactivation more effective by thermal processing. Both thermal and non-thermal processing allowed cold storage for more than 15 days. Abstract: This study evaluated the effects of High-Temperature Short Time (HTST), Ultra High Temperature (UHT), and the non-thermal processes High Power Ultrasound (US), UV-pulsed-light and Low Pressure Plasma (LPP) on the composition, stability, and bioactive compounds bioaccessibility of açai juice. 1H NMR based approach, coupled to chemometrics, was applied to evaluate the changes in the juice composition. All the non-thermal processes increased the sugars content (glucose and fructose), and the amino acid betaine, except the combined processing of ultrasound followed by low-pressure plasma (US.LPP). HTST and UHT increased the fatty acids and phenolic compounds content in the açai juice. The bioaccessibility of phenolic compounds decreased due to the processing. After thermal sterilization (UHT), the anthocyanin bioaccessibility was 2-fold higher. The combined non-thermal treatment reduced the biocompounds bioaccessibility to 40% of the non-processed juice. However, the combined US.LPP improved the bioaccessibility of vitamin C by 8%. UHT increased the anthocyanin's bioaccessibility but sharply decreased vitamin C bioaccessibility. Higher impact of thermal processing on vitamin C, anthocyanins, total phenolics, PPO, POD, DPPH, ABTS, and FRAP was verified after 45 and 60 days of storage compared to the non-thermally processed samples.